Green Synthesis and Spectroscopic Study of New Heterocyclic Compounds Derived from Ethyl Coumarilate - Karm A. Khalaf; Adnan O. Omar (African Journal of Advanced Pure and Applied Sciences, 2023)
The common starting compound ethyl coumarilate and substituted (1,2,3) prepared by the reaction of substituted salicylaldehydes with ethyl chloroacetate in the presence of base the treatment of (1,2,3) with hydrazine hydrate give 2,3a-dihydro-3H-benzofuro[3,2-c]pr azol-3-one (4, 11&18) derivative. But when the ester (1,2,3) reacted with phenyl hydrazine form 2-phenyl-2,3a-dihydro-3H-benzofuro[3,2-c) pyrazol-3-one (5, 12&19). Similar type of reaction occurs with urea, thiourea, guanidine, semicarbazide, thiosemicarbazide, to produce benzofuro [3,2-d] pyrimidine-2,4(3H,4aH)-Dione (6, 13&20). 2-thioxo-2,4a-dihydrobenzofuro [3,2-d] pyrimidin-4(3H)-one (7, 14&21). 2-imino-2,4a-dihydrobenzofuro [3,2-d] pyrimidin-4(3H)-one (8, 15&22), 3-oxo-3,3a-dihydro-2H-benzofuro [3, 2-c] pyrazole-2-carboxamide (9, 16&23), 3-oxo-3,3a-dihydro-2H-benzofuro[3,2-c] pyrazole-2-carbothioamide (10, 17&24) derivatives were synthesized in good to excellent yield under ultrasonic irradiation. The structures of all synthesized compounds in this study have been established by using FT-IR, 1H NMR, and 13C NMR techniques